Modeling and experimental study on the force of micro-milling titanium alloy based on tool runout. Issue 1 (October 2016) - Li, Guo; Qu, Da; Feng, Wei; Wang, Bo; Li, Na
Abstract Geometry defect of tools and assembling error (such as tool runout) is inevitable in the machining process and cannot be ignored in micro-milling processing mechanism. Besides, it also impacts the micro-milling force. Therefore, it plays an important role on impacting surface quality in micro-milling. In the present paper, the milling force model is established for the micro-milling process with considering tool runout, undeformed chip thickness, tool slope angle, shear angle, friction angle, and equivalent rake angle. The model for three-directional micro-milling force is proposed. Furthermore, the cutting forces with different tool runouts are analyzed. The formation of the step that is on the surface and found in the experiments is made clear. Titanium alloy is applied in a series of micro-milling experiments to verify the model of micro-milling force with analyzing the step widths of machined groove edges. The micro-milling process is further comprehended though the model. It helps to judge the surface quality that is affected by tool runout though the analysis of variation of milling force.